ANALISIS PENGARUH ANALISA FUNDAMENTAL DAN RISIKO SAHAM DALAM MENENTUKAN KEPUTUSAN INVESTASI SAHAM JANGKA PENDEK ATAU JANGKA PANJANG: STUDI KASUS PADA 3 SEKTOR UNGGULAN DI BEI - Respati Adimas Gumilang; Vietha Devia SS (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The capital market as a forum for investors in trading stock securities has an important role in the economy. When making a long short term investment decision, investors must pay attention to several aspects as well as investment risks and the fair price of shares. Public knowledge of the capital market is still low so that it becomes a problem in making a long short term investment decision. This study aims to find out how the influence of fair stock value, risk tolerance, and risk perception variables on long-term or short-term investment decisions in the financial, industrial, and non-primary consumer goods sectors. This study used 133 populations of which 114 of the 133 populations invested in the financial sector, 100 invested in the industrial sector and 102 invested in the non-primary consumer goods sector. This study uses a quantitative research approach. The data analysis method used uses multiple linear regression analysis techniques. The research results obtained show that in the long run it is necessary to determine the fair price of shares when making investment decisions so as not to experience losses in the future, while in the short term it is not necessary to determine the fair price of shares but to pay attention to sentiments related to the country's economic conditions. It is also hoped that investors will pay attention to the aspect of risk tolerance so that investors do not make decisions only from the investors' thoughts and perspectives